Monarquía, matrimonio, sucesión y legitimación del poder (siglos V-VII) (Estudios de Historia de España, 2016)
During the Spanish Late Antiquity, we traveled through diferent matters, for instance the actual rol of princeses in the legitimation of new kings, aswell the kind of royal weddings of Frank kings and goths princeses, during the arrian period. Otherwise, how this mixed marriages failled. Besides, a review about the problem of dinastic transfer of power, even in an elective monarchy.
Keywords: Monarchy; Lineage; Succession; Legitimation; Marriage